Predicting beam transmission using 2-dimensional phase space projections of hadron accelerators - Tran, Anthony; Hao, Yue; Mustapha, Brahim; Martinez Marin, Jose L. (Frontiers in Physics, 2022)
We present a method to compressed the 2D transverse phase space projections from a hadron accelerator and use that information to predict the beam transmission. This method assumes that it is possible to obtain at least three projections of the 4D transverse phase space and that an accurate simulation model is available for the beamline. Using a simulated model we show that, a computer can train a convolutional autoencoder to reduce phase-space information which can later be used to predict the beam transmission. Finally, we argue that although using projections from a realistic non-linear distribution produces less accurate results, the method still generalizes well.